Desorption kinetics and speciation of Zn, Pb and Cd in a soil contaminated by mining activities amended with calcite, phosphate, biochar and biosolids - Gomes, Frederico Prestes (2019)
Mining areas produce large amounts of waste that are important sources of potentially toxic elements (PTE), such as heavy metals. These PTEs can contaminate the environment and cause serious threats to the ecosystem and human health. The in-situ remediation by the addition of amendments is an efficient alternative for the immobilization of contaminants and for reduction of the risks associated with these pollutants. Phosphate, lime, and organic compounds are the most used amendments for in-situ remediation. We evaluated the effect of rates of amendments in desorption kinetics and speciation of Zn, Cd, and Pb in a soil contaminated by mining activities. The soil was collected in a disabled Zn mining area in the city of Vazante, state of Minas Gerais, Brazil. The contaminated soil was incubated with either phosphate, or calcium carbonate, or biochar, or biosolid. Desorption kinetics was evaluated by the \"stirred-flow\" method that consists of a constant flow with a Mehlich-3 solution. The speciation was performed by X-ray absorption spectroscopy (XAS) and sequential extraction. The analysis with synchrotron radiation X-ray absorption near the edge (XANES) was performed for Pb and Zn. We also performed a mapping by μ-XRF (micro X-ray fluorescence) and in some spots on the map we performed the speciation by μ-XANES for Zn in the soil amended with phosphate. An experiment with columns was carried out with samples from the soil amended with phosphate to evaluate leaching of Zn, Pb, and Cd. The treatment with phosphate affected the species of Zn. However, some Zn species that were formed and can be mobilized most easily. Zn was more easily mobilized in the highest rate of phosphate probably because of the decrease of the pH. The treatments with biosolid, biochar and calcite did not change Zn species. However, in some rates, Zn desorption decreased while Zn contents increased in the recalcitrant fraction. The main species in the unamended soil was Pb-bentonite and anglesite. The soil amended with calcite and pyromorphite decreased the desorption kinetics of Pb and increased the Pb extracted in the residual fraction, and this could be due to formation of pyromorphite. The soil amended with biosolid and biochar increased the Pb extracted in the organic fraction and decreased in the residual fraction. In these treatments part of the species of Pb present on this soil was transformed in Pb-citrate. The addition of biochar and biosolid increased the desorption kinetics of Pb in all rates applied. The treatment with either biochar or biosolid was effective to decrease the Cd desorption. In these organic amendments, the content of Cd associated to organic matter (OM)increased. The treatments with phosphate and calcite also increased the Cd associated to OM extracted in the F3. These inorganic amendments were effective to decrease the desorption kinetics of Cd.